Inhibitors in Building Students’ Islamic Characters of Halal Tourism Destination at State Senior High School in East Lombok Regency - Mulyani, Isni; wilis, Ratna (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research was aimed to identify inhibiting factors of students' islamic character building at a senior high school in halal tourism destination area in East Lombok. The researcher used a Mix Method research for investigating the inhibitors. Then the priority of those factors were determined by using Urgency Seriousness Growth (USG) technique. To decide alternative solution of the factors the researcher employed Mc Namara which was used on the results obtained from Focus Group Discussion (FGD). The research population was SMA Negeri 1 Sembalun which is located in an area recognized as World's Best Halal Honeymoon Destination by World Halal Tourism Awards in 2016.The sample of qualitative research was chosen through snowball sampling technique on students of senior high schools in East Lombok. Meanwhile, the quantitative research population was all schools 'teachers and the head masters and the sample was chosen by using purposive sampling technique. The qualitative sample generalized the inhibiting factors and provided alternative solutions of the problems. This research can be source information and suggestion in building students' Islamic character especially in areas with halal tourism potentials. As for teachers it can be a reference and additional knowledge especially in solving the problems in building the characters. Furthermore, it also becomes a consideration to help improving the quality of geography learning especially for the sake of student's Islamic character building.